Crossing Feasibility Study Between Sea Freight Vehicles Port-Port of Sheet Anchor Situbondo lombok.we - Sudarso, Soni; Mudjanarko, Sri Wiwoho; Moetriono, Hary; Oetomo, Wateno (Inscientech: Journal of Industrial, Science and Technology, 2017)
Sea Crossing feasibility Study for goods transport Vehicles of All Sheet Anchor, intends to assess the feasibility of the economic aspects, in order to be an attraction for employers to transport equipment whether or not to divert the route. Anchors Port Development crossing so be crossing ferry port with direct destination Lombok West Nusa Tenggara. And the continuous movement of interest NTB-NTT through the island of Bali, which is an icon of Indonesian tourism is no longer burdened with freight vehicles. So relevant to the national program by the Indonesian government Toll Marine present.               By calculating the operating costs of freight vehicles will be known to the costs actually incurred by the transport of goods between Asembagus effort Situbondo - Sheet Harbor NTB through these crossings Ketapang - Gilimanuk, Bali continued crossing padangbai - Sheet Harbor Rp. 5,380,338, -. While crossing rates crossings between Surabaya - Lombok through the port of Tanjung Perak port towards sheets of Rp 4.574 million, - for class freight vehicles of the same.               So if held crossings of freight from the Port Anchors in Situbondo Asembagus toward Sheet Harbor lombok.we or otherwise will be much more economically feasible to be realized. This study could be the basis of information from public policy to support the national development program.   Keywords: Feasibility Study, Route Freight Vehicles Land-Sea, Vehicle Operating Costs